THU0577 Welsh National Audit of 2013 Eular Recommendations on The Management of Medium-High Dose Steroid Use in Rheumatic Diseases. (9th June 2015) - Zaman, M.
Abstract : Background: In 2013 EULAR published consensus and evidence based recommendations on the management of patients who take higher doses of glucocorticoids (GCs) i.e. ≥7.5mg od. The risk-benefit balance for higher doses is purported to be different to that of lower doses. These recommendations cover not only monitoring but education, prevention and dosing considerations. This national study evaluated the compliance of Welsh rheumatology practice with the recommendations made by EULAR. Given the deficiency in studies clarifying prevalence rates of adverse effects (AEs) from prolonged GC exposure, particularly ones which do not lead to hospitalization or require specific treatment, we assessed prevalence rates of AEs associated with GCs as well. Objectives: Assess compliance of Welsh Rheumatology practice with 2013 EULAR recommendations for management of patients on long term higher dose GCs. Assess prevalence rates of GC related AEs in Wales. Methods: Patients with rheumatic conditions on prednisolone ≥7.5mg od for more than 3 months were recruited from all rheumatology centres in Wales between Nov '13–Apr' 14. Data was collected on demographics, GC dosing, patient reported AEs, physician reported AEs, information sharing on GC use, safety & prevention measures, compliance with EULAR monitoring (blood pressure, fasting BM, weight/BMI, cholesterol) and bone protection measures. Appropriate monitoring was defined as patients who were assessed for all EULAR parameters. Results: 165 out of 205 subjects met the inclusion criteria with a 3:1 female:male ratio, mean age 66 years. Mean GC dose was ∼12.5mg od with most patients on GCs for >12 months (60%). The commonest patient reported AEs were weight gain (62%), skin changes (59%), sleep disturbance (54%) & mood changes (39%). Hypertension (24%), pedal oedema (18%) and hyperlipidaemia (15%) were the commonest physician reported AEs. 1/3 of the cohort met all monitoring recommendations (BMs, BP, Weight, Lipids, DEXA/Bone protection); the least commonly measured ones were blood glucose and Lipids. Education on wound care, exercise and diet were 8%, 16% & 18% respectively. Mean Likert score for how well patients felt GC related AEs were explained to them was 4.75. Only 33% recollected being provided a steroid information leaflet. Only 13% were appropriately monitored meeting all EULAR points including educational recommendations. Conclusions: Weight gain and cardiovascular complications were commonly reported AEs which likely reflects the rationale behind the EULAR monitoring recommendations. However several prevalent patient reported AEs are not considered including skin and mood changes and insomnia. Overall, monitoring of clinical measures was reasonable but only 13% met all recommendations (clinical & educational). There is a clear need to improve the standard of care of GC related AEs and patients are expecting better information sharing regarding the drugs they are treated with. We suggest a protocol mirroring the EULAR guidance to be kept in all outpatient rooms and an information poster in clinic waiting rooms. We have also designed a steroid monitoring booklet incorporating all the recommendations to be used in primary and specialist care settings. References: Duru N, et al. EULAR evidenced-based and consensus-based recommendations on the management of medium to high-dose glucocorticoid therapy in rheumatic diseases. Ann Rheum Dis;2013;0:1-9 Disclosure of Interest: None declared